This preview shows page 1. Sign up to view the full content.
Unformatted text preview: k > 0. This leaves the case k =μ 2 , where μ > 0. In this case X ±± + μ 2 X = 0 ⇒ X = c 1 cos μx + c 2 sin μx ; X (0) = 0 ⇒ 0 = c 1 ; X = c 2 sin μx ; X ± ( L ) = 0 ⇒ 0 = c 2 μ cos( μL ) ⇒ c 2 = 0 or cos( μL ) = 0 . To avoid the trivial solution, we set cos( μL ) = 0, which implies that μ = (2 k + 1) π 2 L , k = 0 , 1 , . . . . Plugging this value of k in the equation for T , we Fnd T ± + μ 2 c 2 T = 0 ⇒ T ( t ) = B k eμ 2 c 2 t = B k e( (2 k +1) π 2 L ) 2 c 2 t . ±orming the product solutions and superposing them, we Fnd that u ( x, t ) = ∞ ± k =0 B k eμ 2 c 2 t = ∞ ± k =0 B k e( (2 k +1) π 2 L ) 2 c 2 t sin ² (2 k + 1) π 2 L x ³ . To determine the coeﬃcients B k , we use the initial condition and proceed...
View
Full
Document
This note was uploaded on 12/22/2011 for the course MAP 3305 taught by Professor Stuartchalk during the Fall '11 term at UNF.
 Fall '11
 StuartChalk

Click to edit the document details